2001
DOI: 10.1097/00006231-200105000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Is the depth correction using the geometric mean really necessary in a 99Tcm-DMSA scan in the paediatric population?

Abstract: Determination of the left to right dimercaptosuccinic acid (DMSA) uptake ratio is theoretically one of the easiest quantitative procedures in nuclear medicine. The quantification can be performed on the posterior view, with or without the lateral view for correction of kidney depth. The geometric mean can also be determined using both the anterior and the posterior views. The aim of this study was to evaluate the occurrence of remarkable differences in the results from quantification of the relative renal func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…First, renography is less reliable when one or both of the kidneys has a low uptake, due to the lower signal-noise ratio (7). A difference in depth of the kidneys is also known to affect the outcome owing to the soft-tissue attenuation (9,12). Second, the presence of renal artery stenosis in most of the subjects and the pharmacological conditions could have effects not readily accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…First, renography is less reliable when one or both of the kidneys has a low uptake, due to the lower signal-noise ratio (7). A difference in depth of the kidneys is also known to affect the outcome owing to the soft-tissue attenuation (9,12). Second, the presence of renal artery stenosis in most of the subjects and the pharmacological conditions could have effects not readily accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…The most accurate assessment of split renal function has always been at the forefront in many papers [14][15][16][17], in the interest of both nuclear medicine physicians and nephrologists and urologists. 99m Tc-DMSA as a very good cortical imaging agent is preferentially taken up by the proximal renal tubule and first part of Henle´s loop.…”
Section: Discussionmentioning
confidence: 99%
“…The quantification of the split renal function can be performed by different mathematical analysis, most often from planar images with compensation for kidney depth based on the geometric mean, which can be determined using anterior and posterior views [15]. In context of quantitative 99m Tc-DMSA imaging, it has been reported that the kidney depth compensation is unnecessary when calculating differential renal function for normally located kidneys in the pediatric population [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations